2003
DOI: 10.5194/acp-3-1609-2003
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the performance of chemistry transport models by comparison with research aircraft observations. Part 1: Concepts and overall model performance

Abstract: Abstract.A rigorous evaluation of five global ChemistryTransport and two Chemistry-Climate Models operated by several different groups in Europe, was performed. Comparisons were made of the models with trace gas observations from a number of research aircraft measurement campaigns during the four-year period 1995-1998. Whenever possible the models were run over the same four-year period and at each simulation time step the instantaneous tracer fields were interpolated to all coinciding observation points. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Thouret et al, 1998;Schnadt Poberaj et al, 2009) or chemistry-transport models (e.g. Law et al, 2000;Brunner et al, 2003;Teyessè-dre et al, 2007). However, recent analyses cast some doubt on the long-term stability of the MOZAIC data; particularly the differences between MOZAIC and NOXAR in 1995-1997(Staufer et al, 2013 and the increase in bias between Frankfurt/Munich MOZAIC and the alpine surface site Zugspitze from 1994-2009 (Logan et al, 2012) raised some concern.…”
Section: Discussionmentioning
confidence: 99%
“…Thouret et al, 1998;Schnadt Poberaj et al, 2009) or chemistry-transport models (e.g. Law et al, 2000;Brunner et al, 2003;Teyessè-dre et al, 2007). However, recent analyses cast some doubt on the long-term stability of the MOZAIC data; particularly the differences between MOZAIC and NOXAR in 1995-1997(Staufer et al, 2013 and the increase in bias between Frankfurt/Munich MOZAIC and the alpine surface site Zugspitze from 1994-2009 (Logan et al, 2012) raised some concern.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for the difference might be related to the horizontal grid spacing of the AQ model (e.g. Brunner et al, 2003). As shown in Table 2, the DEHM model, which has the coarsest horizontal grid resolution, simulated the lowest mixing ratios, whereas the CAMx and CMAQ models, with much smaller horizontal grid spacing, simulated the highest mixing ratios.…”
Section: Mean Vertical Profilesmentioning
confidence: 98%
“…This could be due to an underestimation of the exchange between the upper troposphere and the lower stratosphere and/or diffusive model errors related to coarse vertical gridding. By contrast, for the case of global-scale chemistry models, Brunner et al (2003) reported a tendency of models to overestimate ozone mixing ratios over NA between 5.5 and 8 km throughout the year (based on the period 1995-1998). However, while those results were averaged over the entire NA continent, here we are comparing regional-scale models at considerably smaller scales, and the different behaviour could simply be attributed to the different grid sizing as well as the different time period.…”
Section: Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…The overestimation of O 3 mixing ratios during the summer months is a wellknown issue and has been described by various model validation studies (e.g. Brunner et al, 2003;Schaap et al, 2008;Ordoñez et al, 2010;Val Martin et al, 2014). Inadequate ozone precursor concentrations and aerosol induced radiative effects (photolysis) have been frequently identified as being the main factors.…”
Section: Discussionmentioning
confidence: 99%